Influence of wastewater treatment level on the seawater quality in the discharge region of Santos Submarine Outfall - Jayme Pinto Ortiz (Revista Ambiente & Água, 2012)
This study aimed to evaluate if in the case of the Santos Submarine Outfall (SSO) there was any environmental benefits relative to potential eutrophication if instead of the primary treatment a CEPT, ST-AS or a TT- ASNR was used. The environmental impact of wastewater discharge through the SSO with an average flow of 5,3 m3.s-1 was evaluated using an eutrophication numerical model which solves the two-dimensional vertically integrated hydrodynamic and transport equation. Wastewater mixing conditions in the near field plume was evaluated using the software CORMIX, and the results were coupled to a far-field model considering the conservation of mass flow. The results demonstrate that the use of a secondary treatment with partial ammonia oxidation promotes a reduction of only 30% in the chlorophyll-a, while the use of a CEPT with phosphate removal promotes a better environmental response, resulting in chlorophyll-a concentration reduction of 69%, similar results were obtained when tertiary treatment was considered for nitrogen and phosphorus removals.